Pengaruh Interior Ambient terhadap Kepuasan Pelanggan Dimediasi oleh Keputusan Pembelian Konsumen di O’Good Coffee dan Eatery - Junior, Junior; Facrureza, Dewanta (MES Bogor, 2024)
Customer satisfaction is a measure of how successful a store is. With high customer satisfaction, it can be ensured that the store we manage can provide financial benefits and operational progress. Customer satisfaction can be enhanced through interior ambient, meaning that if the interior ambient of a store is good, it will increase the percentage of customer satisfaction visiting a store. The inside surrounding of a store should be very much arranged and executed to boost the consequences of the arranged inside encompassing to give close to home consolation that causes clients to feel great in a store. Notwithstanding inside encompassing, buy choices can likewise increment customer fulfillment since shopper fulfillment is gotten after buy choices are made. In this review, the impact of inside encompassing on consumer loyalty intervened by buy choices will be inspected, dissected, and tried. This examination was led utilizing quantitative strategies and a logical exploration approach. An example of 120 individuals was gathered utilizing a survey containing proclamations with a Likert scale. The actual example comprised of individuals who had visited, executed, and remained at O'Good Espresso and Restaurant. The gathered information was then breaking down and tried utilizing the Fractional Least Square (PLS) approach. As per the examination and testing results led through the gathered information, it is shown that inside encompassing affects consumer loyalty and buy choices are demonstrated to have the option to be factors in the connection between inside surrounding and consumer loyalty.